Probiotic properties of Bacillus subtilis DG101 isolated from the traditional Japanese fermented food nattō - Leñini, Cecilia; Rodriguez Ayala, Facundo; Goñi, Anibal Juan; Rateni, Liliana; Nakamura, Akira; Grau, Roberto Ricardo (Frontiers in Microbiology, 2023)
Spore-forming probiotic bacteria offer interesting properties as they have an intrinsic high stability, and when consumed, they are able to survive to the adverse conditions encountered during the transit thorough the host gastrointestinal (GI) tract. A millenarian healthy food, Nattō, exists in Japan consisting of soy fermented by the spore-forming bacterium Bacillus subtilis natto. The consumption of Nattō is linked to many beneficial health effects, including the prevention of high blood pressure, osteoporosis, and cardiovascular-associated disease. We hypothesize that the bacterium B. subtilis natto plays a key role on the beneficial effects of Nattō on humans. Here, we present the isolation of B. subtilis DG101 from Nattō and its characterization as a novel spore-forming probiotic strain for human consumption.B. subtilis DG101 was non-hemolytic, showed high tolerance to lysozyme, low pH, bile salts, and strong adherence ability to extracellular matrix proteins (i.e., fibronectin and collagen), pointing out its potential application for competitive 2 exclusion of pathogens. B. subtilis DG101 forms robust liquid and solid biofilms and expresses several extracellular enzymes with activity against food diet-associated macromolecules (i.e., proteins, lipids, and polysaccharides) that would be important to improve food diet digestion by the host. B. subtilis DG101 was able to grow in the presence of toxic metals (i.e., chromium, cadmium, and arsenic) and decreased their bioavailability, a feature that points to this probiotic as an interesting agent for bioremediation in cases of food and water poisoning with metals. In addition, B. subtilis DG101 was sensitive to antibiotics commonly used to treat infections in medical setting, and at the same time it shows a potent antimicrobial effect against pathogenic bacteria and fungi. In mammalians (i.e., rats), B. subtilis DG101 colonized the GI tract, and improve the lipid and protein serum homeostasis of animals fed on the base of a normal-or a deficient-diet regime (dietary restriction).In the animal model for longevity studies, Caenorhabditis elegans, B. subtilis DG101 significantly increased the animal lifespan and prevent its age-related behavioral decay. Overall, these results demonstrate that B. subtilis DG101 is the key component of Nattō with interesting probiotic properties to improve and protect human health.